Patient care after heart transplantation - a case study - BOŻENA MAJCHROWICZ (Journal of Education, Health and Sport, 2022)
Heart transplantation is a recognized and effective method of treating end-stage heart failure. Complicated heart transplant surgery carries a high surgical risk as well as complications that are dangerous to life and health. Transplantation is a life-saving opportunity for patients who have run out of alternative treatments. Patients with heart transplants face many physical and psychological problems every day.